Lectin‐Array Blotting. Issue 1 (1st September 2017) - Pazos, Raquel; Echevarria, Juan; Hernandez, Alvaro; Reichardt, Niels‐Christian
Abstract: Aberrant protein glycosylation is a hallmark of cancer, infectious diseases, and autoimmune or neurodegenerative disorders. Unlocking the potential of glycans as disease markers will require rapid and unbiased glycoproteomics methods for glycan biomarker discovery. The present method is a facile and rapid protocol for qualitative analysis of protein glycosylation in complex biological mixtures. While traditional lectin arrays only provide an average signal for the glycans in the mixture, which is usually dominated by the most abundant proteins, our method provides individual lectin binding profiles for all proteins separated in the gel electrophoresis step. Proteins do not have to be excised from the gel for subsequent analysis via the lectin array but are transferred by contact diffusion from the gel to a glass slide presenting multiple copies of printed lectin arrays. Fluorescently marked glycoproteins are trapped by the printed lectins via specific carbohydrate‐lectin interactions and after a washing step their binding profile with up to 20 lectin probes is analyzed with a fluorescent scanner. The method produces the equivalent of 20 lectin blots in a single experiment, giving detailed insight into the binding epitopes present in the fractionated proteins. © 2017 by John Wiley & Sons, Inc.